Application of PCR Sequencing and Next-Generation Sequencing in the Diagnosis of Sporotrichosis - Yang X; Yang X (Clinical, Cosmetic and Investigational Dermatology, 2024)
Xinyu Yang, Xiumin Yang Department of Dermatology, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Xiumin Yang, Email YXM8092@163.comAbstract: Sporotrichosis is a common chronic fungal infection and the clinical manifestations are often untypical. Diagnosis of sporotrichosis relies conventionally on fungal culture, histopathological examination, and species identification by molecular test. We reported that a 70-year-old man presented with a cutaneous lesion on the back of his right hand (present for 6 months). The cutaneous bacterial infection was diagnosed at a local hospital and the lesion had not improved. Physical examination revealed an infiltrative reddish plaque with purulent secretion and crusts. Histopathological examination revealed scattered round yeast cells in the dermis. Fungal culture revealed multiple, velvety, brown colonies on Sabouraud dextrose agar (SDA). Sporothrix globosa was identified by PCR-sequencing and next generation sequencing (NGS) method. Finally, a case of sporotrichosis caused by Sporothrix globosa was diagnosed by histopathological examination, mycological examination, and molecular identification. The patient was treated with oral itraconazole 400 mg/day for 2 months. The lesion was dramatically ameliorated.Keywords: sporotrichosis, PCR sequencing, next generation sequencing